Dynamic Evaluation of Carbon Emission Performance of New Energy Enterprises based on Orthogonal Projection Method. (27th August 2022) - Wang, Tinggui; Li, Hemei
Abstract : The rapid development of economic society causes people to increase the energy demand, produce more and more carbon dioxide, environmental pollution is becoming more and more serious, to solve the problem of carbon peak is imminent. Under the same and complete evaluation system, the carbon emission performance varies slightly according to different R&D directions of new energy enterprises. Therefore, it is particularly important to select evaluation indicators. In fact, each enterprise has different efforts to control carbon emissions. While studying the performance of carbon emissions, the direct and indirect impacts of carbon dioxide produced by each enterprise in the process of production on the ecological environment should be considered. In order to guarantee systematic and scientific outcomes, carbon emissions performance evaluation indicator system for new energy enterprises is constructed. With new energy enterprises as examples, based on the construction of carbon emissions performance evaluation indicator system of new energy enterprises, orthogonal projection method is used to carry out an empirical analysis of the dynamic evaluation of carbon emissions performance of thirty new energy enterprises. Through the questionnaire survey of thirty new energy enterprises, the indicator weight of carbon emission performance evaluation of new energy enterprises was determined, and the carbon emission performance of new energy enterprises was analyzed. The results will reflect the actual situation of China's new energy enterprises, and provide the data support and references for future research on carbon emission control by the country and enterprises.